Studi Kasus Penyelenggaraan dan Pengelolaan Ekstrakurikuler Olahraga di SMP Negeri 1 Muntilan Kabupaten Magelang - Aditya, Hani; Qoriah, Anirotul (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to describe the implementation and management of sports extracurricular activities at SMP Negeri 1 Muntilan, Magelang Regency and to describe the constraints on the implementation of sports extracurricular activities at SMP Negeri 1 Muntilan, Magelang Regency. The results of this study that extracurricular management at SMP Negeri 1 Muntilan has gone well with the obtaining of attendance journals and training programs, but in organizing at SMP Negeri 1 Muntilan, Magelang Regency, only a part has an organizational structure that specifically handles extracurricular activities. The obstacles faced in implementing extracurricular activities include; time, infrastructure, weather and equipment financing. The conclusion in this study is that the management of sports extracurricular activities at SMP Negeri 1 Muntilan has been going well with the discovery of an existing journal of attendance and training programs and the obstacles faced in implementing sports extracurricular activities at SMP Negeri 1 Muntilan, namely; time, facilities and infrastructure, as well as the weather and the less enthusiastic interest of female students.